Antidiabetic and Hypolipidemic Effects of Extracts of Gymnema Sylvestre in Streptozotocin Induced Type I Diabetes in Rats - Mahida, Nishtha R.; Mandali, G.C.; Sindha, Vijaysinh V.; Raval, S.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Gymnema sylvestre of the family Asclepiadaceae is one of the most important medicinal plants of the central eco-region. It is popularly known as Gurmar, which means “sugar killer”. Extract of leaves is reported to have tannins, gum, flavonoids, proteins and saponins. It has displayed a wide array of pharmacological activities. This study was aimed to investigate the antidiabetic and hypolipidemic effects of Gymnema sylvestre extract in experimentally induced diabetes in rats. Diabetes was produced in adult Wistar rats with single dose of streptozotocin (STZ) @ 60 mg/kg b.wt. intraperitoneally. After the confirmation of diabetes on 7th day (sugar >200 mg/dl), alcoholic and aqueous extracts of G. sylvestre (400 mg/kg) were administered orally to the experimental rats from 8th day and continued for 42 days thereafter. The antidiabetic and hypolipidemic activity was estimated by measuring blood glucose, lipid profile and histopathological examination of various tissues from all the groups. Administration of STZ resulted in a significant (p
Keywords: Diabetes mellitus; Gymnema sylvestre; Streptozotocin; Blood glucose; Lipid profile